Starter vegetable gardens : 24 no-fail plans for small organic gardens - Pleasant, Barbara (Storey Publishing, 2023)
"Detailed planting and care designs for 24 beginner-friendly gardens, from what to buy, where and when to plant, and how to care for each vegetable"--